Effects of acute aerobic exercise on motor response inhibition: An ERP study using the stop-signal task - Chien-Heng Chu; Brandon L. Alderman; Gao-Xia Wei; Yu-Kai Chang (Elsevier, 2015)
Purpose: The purpose of this study was to determine the effects of acute exercise on motor response inhibition using both behavioral and electrophysiological approaches. Methods: The P3 and N1 event-related potential (ERP) components were recorded while performing a stop-signal task in 21 college students following a moderately intense acute exercise bout for 30 min and a sedentary control session that involved reading. Results: Acute exercise induced a shorter stop signal response time (SSRT) as compared to control; however, the go response time (Go RT) remained unchanged. In examining the ERP data, acute exercise increased both P3 amplitude and latency but did not affect the N1 component. Conclusion: Acute exercise has a selective and beneficial effect on cognitive function, specifically affecting the motor response inhibition aspect of executive function. Furthermore, acute exercise predominately impacts later stages of information processing during motor response inhibition, which may lead to an increase in attentional resource allocation and confer the ability to successfully withhold a response to achieve motor response inhibition.